2010
DOI: 10.1007/s10529-010-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed synthesis of two new antioxidants: 4-O- and 3-O-palmitoyl chlorogenic acids

Abstract: Chlorogenic acid (5-caffeoyl quinic acid (CQA)) extracted from Hydrangea macrophylla (44%, w/w) with 98% purity, was acylated with palmitic acid by Novozym 435 to yield mono-acylated CQA. Acylation of CQA was achieved in 2-methyl-2-butanol at 60°C, and yielded two mono-acylated products: a major product acylated at the C-4 of the quinic moiety (4-O-palmitoyl chlorogenic acid) and a minor product acylated at the C-3 (3-O-palmitoyl chlorogenic acid). The bioconversions obtained in 7 days ranged from 14 to 60% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Previous reports have shown that the lipophilic derivatives and analogs of one of the olive phenols, HT, with esters or ethers functionalities display a better hydrophilic/lipophilic balance [28], an increased bioavailability compared with their unprotected analogs [29] and stability to oxygen compared with the underivatized HT, which make these molecules more attractive for the food industry [30]. These findings prompted us to develop three innovative aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that the lipophilic derivatives and analogs of one of the olive phenols, HT, with esters or ethers functionalities display a better hydrophilic/lipophilic balance [28], an increased bioavailability compared with their unprotected analogs [29] and stability to oxygen compared with the underivatized HT, which make these molecules more attractive for the food industry [30]. These findings prompted us to develop three innovative aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning CQA acyl esters, 4-O-palmitoyl-CQA and 3-O-palmitoyl-CQA display similar free radical scavenging activities, equivalent to 70-80% of CQA activity [7]. Interestingly, activity of CQA acyl esters was as much as five times higher than butylhydroxytoluene activity, a common synthetic antioxidant added to food.…”
Section: Ester Chlorogenate Antioxidant Propertiesmentioning
confidence: 97%
“…and palmitic acid in 2methyl-2-butanol using Novozym 435m at 608C [7]. and palmitic acid in 2methyl-2-butanol using Novozym 435m at 608C [7].…”
Section: Enzymatic and Chemo-enzymatic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their antioxidant and other biological effects [6][7][8], convenient methods of CQAs have been sought for practical synthesis. As a result, numerous scientific papers have been published on the chemical and enzymatic synthetic methods, such as by Hemmerle et al [9] and Lorentz et al [10] Among these methods, Sefkow and co-workers' [11,12] have reported for the first time a complete package of CQAs syntheses. They synthesized 1-, 3-, 4-, and 5-CQA with performing esterification of suitable protected quinic acids with acid chloride of caffeic acid.…”
Section: Introductionmentioning
confidence: 99%